Attitude of Teachers towards Informal Education: A Comprehensive Review - Monu Kumari; Md Emdadul Hoque; Praveen Rastogi (Educational Administration: Theory and Practice, 2024)
Informal education plays a crucial role in complementing formal education by fostering creativity, critical thinking, and experiential learning. This review explores teachers’ attitudes towards informal education, analyzing its perceived benefits, challenges, and integration strategies. Data is synthesized from academic studies, surveys, and policy reports to provide a comprehensive understanding of the subject. Key findings indicate that while teachers recognize the value of informal education in enhancing student engagement and problem-solving skills, challenges such as lack of institutional support, difficulty in assessment, and resource constraints hinder its widespread adoption. The study also highlights successful integration strategies, including project-based learning, digital platforms, and peer mentoring. Policy reforms and targeted teacher training programs are recommended to enhance acceptance and implementation. Future research should focus on longitudinal studies, cross-cultural comparisons, and the role of emerging technologies in informal learning.